Next generation shotgun sequencing and the challenges of de novo genome assembly - Stephen Schlebusch; Nicola Illing (South African Journal of Science, 2012)
Sequencing the genomes of the many scientifically fascinating plants and animals found in South Africa is fast becoming a viable option as a result of the rapid and sustained drop in the cost of next generation sequencing over the last five years. However, the processing and assembly of the sequence data produced is not trivial. There are several factors which need to be taken into consideration when planning a strategy to assemble genome sequence data de novo. This paper reviews the advances and the challenges in two of the most rapidly developing areas of the field: the sequencing technology and the software programs used to assemble de novo the sequence data generated by these technologies into a genome.